Characterization of Stagonosporopsis cucurbitacearum and field evaluation of a new coded fungicide (XDE-659) efficacy against gummy stem blight on watermelon in Malaysia - Abdul Aziz, Waziri (2021)
Gummy stem blight (GSB) disease is caused by Stagonosporopsis cucurbitacearum fungus. It is the most destructive disease in most of the watermelon-producing areas of Malaysia. This study was aimed to characterize the S. cucurbitacearum fungus based on morphological and molecular characteristics, to assess the pathogenicity of S. cucurbitacearum isolates on watermelon in vitro and in planta assays as well as to assess the control efficacy of the new coded fungicides. Ten isolates of S. cucurbitacearum were obtained from infected watermelon leaves and stems from two different locations; Ladang 15, UPM and MARDI, Selangor, Malaysia. The isolates were identified based on morphological and molecular identification. The pathogenicity test (in vitro and in vivo) was carried out on Red Rocky watermelon seedlings. The efficacy of the new coded fungicides that developed by Dow AgroSciencesTM was evaluated in the field. For morphological characteristics, potato dextrose agar (PDA) and chickpea seed agar (CSA) media were used to assess these isolates. From the top view of petri dish, fungal colony appeared as white, gray and olivaceous mycelia while from bottom view of petri dish, the colony was initially white and later turned to olivaceous green or black with concentric circles. The conidial shapes of these isolates were mainly oblong round with hyaline and smooth growth. These spores were having average size of 5-14 μm (length) and 3-5 μm (width), therefore, the isolates were identified as S. cucurbitacearum. The molecular identification using internal transcribed spacer region (ITS1-5.8S-ITS2), and a partial sequence of the β-tubulin (TUB) gene have confirmed the ten isolates as S. cucurbitacearum. The ten isolates were selected for pathogenicity tests based on in vitro and in planta inoculation assays on healthy watermelon plants. The isolates M1, M2, M3, M4, M5, M6 and M7 that obtained from MARDI were significantly more virulent based on the size of the lesions formed after inoculation. While the isolates M8, F1 and L were found to be the least aggressive among the isolates tested by having small lesions on leaves and stems. For efficacy evaluation of the new coded fungicides, GF 3716, GF 3540, GF 3542 and Amistartop® (standard fungicide) were used to manage GSB. The results show that all the coded fungicides were found to be effective and have reduced the disease severity in watermelon plants as compared to the untreated control. Trt 1 (GF 3716/1500 mL/ha), Trt 5 (tank mix of GF3540/1500 mL/ha + GF3542/600 mL/ha) and Trt 6 (tank mix of GF3540/1000 mL/ha + GF3542/400 mL/ha) and Trt 10 (tank mix of GF3540/1000 mL/ha + Adsee C80W/ 250 mL/ha) were significantly (P < 0.05) effective in reducing the GSB disease severity where these fungicides provided higher control efficacy with 77.45, 79.41, 74.5 and 76.47%, respectively, as compared to the standard and untreated control. Moreover, Trt 2 (GF3716/1000 mL/ha), Trt 3 (GF3716/750 mL/ha) and Trt 7 (tank mix of GF3540/750 mL/ha + GF3542/300 mL/ha) showed a high control efficacy with 70.58, 68.62 and 66.66%, respectively, as compared to the rest of the treatments. Trt 4 (GF3716/500 mL/ha), Trt 8 (GF3540/500 mL/ha + GF3542/200 mL/ha) were not significantly different from standard fungicide. However, Trt 9 (GF3540/1000 mL/ha + GF3542/0.3 mL/ha) has the least control efficacy as compared to all coded treatments and standard except the untreated control treatment. In conclusion, the findings of morphology and molecular characterization have identified the pathogen as S. cucurbitacearum, more so, the products with XDE-659 as an active ingredient and a tank-mix of adjuvant with the highest application rate had a higher potential to control GSB disease caused by S. cucurbitacearum in watermelon farm.